A hybrid multi-criteria analysis of energy efficient CO2 iron making technologies with carbon capture and storage / Md Abdul Quader - Md Abdul , Quader (2015)
An increase in CO2 emissions to the atmosphere from the fossil fuel based industries has contributed serious global warming problems. Among several greenhouse gases (GHGs), CO2 is the prime contributor and accounts for approximately 60% of the greenhouse effect due to its immense amount of discharges. The iron and steel industry is known as the largest energy consuming manufacturing sector, contributing 5% of the world’s total energy consumption. Also, this industry is emitting about 6% of the total world anthropogenic CO2. Therefore, investigation, development and deployment of alternative energy-efficient iron-making breakthrough technologies along with CO2 capture technologies are receiving high priority to mitigate GHG emissions around 50% by 2050 compared to 2007 level. A new hybrid Multi-criteria Decision Making (MCDM) model was proposed to evaluate the CCS systems in the iron and steel making processes. This model successfully identifies the important optimal criteria and selects the best alternative iromaking technology by considering four prominent aspects (engineering, economic, environmental and social) of sustainability. Surveys questionnaire had been conducted with groups of experts having relevant experience. The model is aimed to transparently and comprehensively measure a wide variety of heterogeneous CCS interdisciplinary criteria to provide insights into aid decision makers in making CCS specific decisions in the iron and steel industry. This proposed MCDM model integrated four methods: Delphi, 2-tuple DEMATEL (Decision making trial and evaluation laboratory), AHP (Analytical hierarchy process) and EFAHP (Extent Analysis method on Fuzzy AHP). A case study was conducted in the iron and steel manufacturing industries in Malaysia to illustrate the application of the framework. This proposed model is flexible with a potential scope of application in similar kinds of energy-intensive industries for the implementation of CCS systems in terms of considered alternatives and criteria.